Gelar "Al-Sahid" Pada Beberapa Nisan Makam Kuna Di Indonesia (Sebuah Interpretasi Baru) - nfn. Mujib (Berkala Arkeologi, 1995)
Three ancient tombs, namely the tomb of Fatimah binti Maymun in Leran, Gresik, East Java dated 475 H (1082 AD), the tomb of Sultan Al-Malik AI-Salih dated 726 H (1326 AD) and the tomb of the queen Nah- Risah bin Sultan Al-Abidin from the numerical year 831 H (1428 AD) is also a descendant of Sultan Al-Malik Al-Salih of Samudra Pasai, North Aceh. When compared to other ancient tombs that have been found and researched in Indonesia that reached hundreds, even thousands in number. The specificity is seen in the form of tombstones, inscription style and the use of laqb (title, abnome) which reflects the Islamic influence, with the use of the title AI-Sahid in front of the names.